Influence of growth rate on nitrogen balance in adolescent sprint athletes - Aerenhouts, D.; Van Cauwenberg, J.; Remi Poortmans, J.; Hauspie, R.; Clarys, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
This study aimed to estimate nitrogen balance and protein requirements in adolescent sprint athletes as a function of growth rate and physical development. Sixty adolescent sprint athletes were followed up biannually over a 2-yr period. Individual growth curves and age at peak height velocity were determined. Skeletal muscle mass (SMM) was estimated based on anthropometric measurements and fat mass was estimated by underwater densitometry. Seven-day diet and physical activity diaries were completed to estimate energy balance and protein intake. Nitrogen analysis of 24-hr urine samples collected on 1 weekday and 1 weekend day allowed calculation of nitrogen balance. Body height, weight, and SMM increased throughout the study period in both genders. Mean protein intakes were between 1.4 and 1.6 g kg-1 day-1 in both genders. A protein intake of 1.46 g kg-1 day-1 in girls and 1.35 g kg-1 day-1 in boys was needed to yield a positive nitrogen balance. This did not differ between participants during and after their growth spurt. None of the growth parameters was significantly related to nitrogen balance. It can be concluded that a mean protein intake around 1.5 g kg-1 day-1 was sufficient to stay in a positive nitrogen balance, even during periods of peak growth. Therefore, protein intake should not be enhanced in peak periods of linear or muscular growth.